Co-Digestion of Tea Extracts with Omega-3 Fatty Acids Enhances Digestive Stability and Intestinal Absorption of Omega-3 Fatty Acids by Increasing Antioxidant Activity and Micelle Stabilization - In-Su Na; Hyun Woo Jeong; Jin-Oh Chung; Byung-Fhy Suh; Jonghee Sohn; Soon-Mi Shim (Applied Sciences)
The current study hypothesized that omega-3 fatty acids ω-3 FAs consumed with various tea extracts, which included green tea extract comprising 35% and 65% catechin (GTE35 and GTE65), naturally fermented green tea (Heukcha) extract (NFGT), and a complex of heat-treated green tea and enzymatically-modified isoquercitrin (1:1, w:w) (AdiphenonTM) would enhance the digestive stability and intestinal absorption of ω-3 FAs. The digestive stability of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) co-digested with GTE65 using an in vitro digestion model system was improved by up to 20.76% and 23.22%, respectively, compared to ω-3 FAs. The oxidative stability, measured using peroxide values, was the lowest, whereas the DPPH radical scavenging capacity during digestion was the highest in Adiphenon™, showing 1.03 ± 0.25 meq O2/kg oil and 1251.96 ± 26.03 µmol TE/g. The deviation in zeta potential was reduced when ω-3 FAs were co-treated with various tea extracts, indicating that the micelle of ω-3 FAs is stable. The intestinal absorption in Caco-2 cells increased by up to 34.53% for EPA and 60.23% for DHA with various tea extracts compared to ω-3 FAs alone. The co-treatment with GTE35 and Adiphenon™ did not alter the expression of P-glycoprotein (P-gp) compared to ω-3 FAs alone, which implies the efflux of tea polyphenols, such as catechins, could be limited due to the suppression of P-gp by ω-3 FA. The results from the current study suggest that the co-intake of ω-3 FAs with various tea extracts could increase the bioavailability of ω-3 FAs by preventing oxidation, stabilizing micelle structures, and minimizing intestinal efflux.